2016
DOI: 10.1038/sj.ebd.6401197
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in aggressive periodontitis, is there a clinical benefit?

Abstract: Data sourcesMedline, Embase and CENTRAL databases were searched up to December 2014. Unpublished data were sought by searching a database listing unpublished studies OpenGray [http://www.opengrey.eu/], formerly OpenSIGLE.Study selectionRandomised clinical trials assessing treatment of patients with AgP comparing scaling and root planing (SRP) alone with SRP plus a single antibiotic or a combination of drugs with a minimum of three months follow-up were considered. Studies specifically designed to evaluate smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…[24] The use of adjunctive antibiotics helps in control of tissue invasive bacteria including A. actinomycetemcomitans and Porphyromonas gingivalis (causative organisms for localized and generalized aggressive periodontitis, respectively). [25] Literature supports the use of a combination of amoxicillin and metronidazole in the adjunctive treatment of aggressive periodontitis. [25]…”
Section: Discussionmentioning
confidence: 99%
“…[24] The use of adjunctive antibiotics helps in control of tissue invasive bacteria including A. actinomycetemcomitans and Porphyromonas gingivalis (causative organisms for localized and generalized aggressive periodontitis, respectively). [25] Literature supports the use of a combination of amoxicillin and metronidazole in the adjunctive treatment of aggressive periodontitis. [25]…”
Section: Discussionmentioning
confidence: 99%
“…Thoden van Velzen et al reported that oral bacteria have 3 different mechanisms of causing non‐oral disease: (i) metastatic infection caused by bacterial translocation; (ii) metastatic damage associated with microbial toxins; and (iii) metastatic inflammation caused by immune injury. DS is one of the standard methods of preventing and treating periodontitis with or without antibiotic administration . PLA formation is thought to result from the transmission of infections through 3 major pathways, namely the biliary tract, portal vein and hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…Although about 50% of liver abscess cases are considered cryptogenic, Yoneda et al reported liver abscess was caused by periodontal bacterial infection with Fusobacterium necrophorum . As periodontitis is typically treated using mechanical dental procedures, including DS, at regular intervals to reduce oral bacteria, which may also decrease the risk of PLA . Taken together, we proposed the hypothesis that PLA is more prevalent in individuals with periodontitis and that DS can reduce the occurrence of PLA.…”
Section: Introductionmentioning
confidence: 92%
“…Decision to refer cases of AgP to specialists for further management can be made if cases are diagnosed accurately in the first instance. The treatment plan for AgP includes oral hygiene instructions and motivation and mechanical therapy, which may be supplemented by systemic antimicrobial therapy,[ 12 13 ] psychological therapy,[ 14 ] assessment of periodontal status of family members,[ 12 ] and plan for long-term maintenance at shorter recall intervals. [ 15 ] Incorrect diagnosis may result in the formulation of a treatment plan without addressing these vital issues.…”
Section: Discussionmentioning
confidence: 99%